A fully integrated CMOS precision full-wave rectifier - Kumngern, Montree (My University, 2016)
This paper presents a new fully integrated high frequency precision full-wave rectifier, which is highly suitable for CMOS technology implementation. The structure comprises a voltage-to-current converter, current rectifiers and a current-to-voltage converter. When an input voltage signal is supplied, it will be converted into two symmetrical current signals by using dual-output operational transconductance amplifier. These current signals will be rectified by using junction diodes that can realize by MOS transistors and convert into an output voltage by using MOS resistor. Hence, the structure can be design by all solid-state. Simulated rectifier results based on a 0.5 μm CMOS technology demonstrates high operating frequency and high precise rectification. Temperature sensitivity of the circuit has also been compensated. Simulation results are included to show workability of the proposed circuit.
Keywords: CMOS; Full-wave; Nonlinear circuit; Precision rectifier